Radioprotective potential of whey protein against gamma irradiation-induced lingual damage - Hassan, Hanaa M.; Abdeen, Asmaa M.; Abdelrahman, Ibrahim Y.; Abdo, Walied; Mohammed, Saher S.; Abdeen, Ahmed; Abdelkader, Afaf; Olga, Rada; Fericean, Liana; Ibrahim, Samah F.; Ghamry, Heba I.; Elgendy, Farouk S.; et al. (Frontiers in Pharmacology, 2023)
This is a provisional file, not the final typeset article Ionizing radiation (IR) is effectively used in the treatment of oral malignancies; however, it might also significantly harm the surrounding tissues. Whey protein isolate (WP) is a protein derived from milk that exhibits a wide range of bioactivities. Therefore, the present research aimed to delineate the mitigating impact of WP against gamma irradiation-induced lingual damage. Rats were randomized into 5 groups: Control (saline, orally, 14 days), WP (WP; 0.5 g/kg b. w., orally, 14 days), IR (saline, orally, 14 days, exposed to 6 and 3 Gy on days 4 and 6, respectively), WP+IR (WP was given orally for 14 days before and after IR exposure; exposed to 6 and 3 Gy on days 4 and 6, respectively), and IR+WP (WP, orally, started 24 h after 1 st IR exposure till the end of the experiment) groups. Samples were collected at two-time intervals (on the 7 th and 14 th days). Oxidative stress was stimulated upon IR exposure in tongue, indicated by boosted malondialdehyde (MDA) level, along with a decrease in the total antioxidant capacity (TAC) level, superoxide dismutase (SOD), and catalase (CAT) activities.Additionally, IR exposure depicted an increase of serum IgE, inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin (IL)-6), along with overexpression mRNA levels of nuclear factor kappa-B transcription factor/p65 (NF-κB/p65), and down-regulation of nuclear factor erythroid 2-related factor 2 (NRF2) and heme oxygenase (HO-1) mRNA levels in tongue tissue. Moreover, IR triggered alterations in lingual histological architecture. The antioxidant and anti-inflammatory properties of WP mitigated oxidative damage, inflammation, and desquamation that were brought on following IR exposure. The protective administration of WP markedly decreases IR-induced lingual harm compared to the mitigation protocol. Our findings recommend WP supplements to the diets of cancer patients undergoing IR that might aid radioprotective effects.